Race, real estate, and uneven development : the Kansas City experience, 1900-2010 - Gotham, Kevin Fox. (Albany : State University of New York Press, 2014)
"Updated second edition examining how the real estate industry and federal housing policy have facilitated the development of racial residential segregation"--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Housing -- Missouri -- Kansas City -- History -- 20th century; Kansas City (Mo.) -- Economic conditions; Kansas City (Mo.) -- Race relations; Electronic books